The Collective Farm‐household Model: Policy and Welfare Simulations. (30th March 2016) - Matteazzi, Eleonora; Menon, Martina; Perali, Federico
Abstract: This study develops a household enterprise model extended to encompass recent advances in collective theory. We use a simulation model in which production and consumption‐leisure choices are represented along with the rule governing intra‐household resource allocation, to analyze the income and wage responses of each family member. The household is treated as an equilibrium model whose accounts are based on a collective household accounting matrix, with the social dimension being the wife/husband classes. The simulation analysis illustrates the policy relevance of the collective approach to household behavior for inferring the impact of economic policies on individual behavior and welfare. We also propose insightful comparisons with the unitary model to make the behavioral and welfare policy relevance of the collective approach evident.